UNIQUE FEATURES OF GENERATING ELECTRCITY FROM SOLAR ENERGY - Maxmudov Mannon Hasanovich (Web of Journals Publishing, 2024)
The Solar Energy is produced by the Sunlight is a non-vanishing renewable source of energy which is free from eco-friendly. Every hour enough sunlight energy reaches the earth to meet the world’s energy demand for a whole year. In today’s generation we needed Electricity every hour. This Solar Energy is generated by as per applications like industrial, commercial, and residential. It cans easily energy drawn from direct sunlight. So it is very efficiency & free environment pollution for surrounding. In this article, we have reviewed about the Solar Energy from Sunlight and discussed about their future trends and aspects. The article also tries to discussed working, solar panel types; emphasize the various applications and methods to promote the benefits of solar energy
Keywords: Renewable energy, Solar panel, Photovoltaic cell, Modelling of PV Panel, Solar Concrete Collector.